Exploring the E-Commerce Corn Dog: an MBKM Program by UIGM Students to Support MSMEs - Apriyanti, Apriyanti; Hertati, Lesi; Asharie, Asmawati; Avini, Terti (International Journal of Social Science and Community Service, 2023)
In facing the ever-growing digital era, Indo Global Mandiri University (UIGM) students, as agents of change, are expected to be able to utilize e-commerce to support the Student-Based Internship Program (MBKM) with a focus on Micro, Small, and Medium Enterprises (MSMEs). This activity, entitled "Exploring E-Commerce MBKM UIGM Students in Supporting the MSME Program," aims to respond to digital business trends and make a positive contribution to local economic development through MSMEs. During the e-commerce exploration process, students actively participate in developing digital solutions and strategies to support MSMEs. The existence of an e-commerce platform is expected to provide added value for MSMEs, increase competitiveness, and expand market reach. The concrete steps involved in this exploration include strategic planning for e-commerce implementation, the development of a website or online trading platform, digital marketing, and performance measurement through data analysis. The application of the MBKM concept helps integrate theoretical learning with practical application, giving students real experience in entrepreneurship. The success of this program is measured through the growth of the MSMEs involved, increased income, and economic empowerment of local communities. Additionally, exploring e-commerce is also an opportunity for students to develop managerial, marketing, and information technology skills that are highly relevant to current market demands.